Profile of Students Collaboration Skills, Critical Thinking, and Cognitive Learning Outcomes - Lianto, Lianto; Lestari, Sri Rahayu; Susanto, Hendra (Jurnal Pijar Mipa, 2025)
Undergraduate graduates must achieve the Indonesian National Qualifications Framework level 6. The graduate profile can be accomplished by enhancing 21st-century competencies, namely collaboration, critical thinking, and cognitive learning outcomes. This study aimed to examine the profile of students’ collaboration, critical thinking skills, and cognitive learning outcomes. This study included 73 students majoring in Biology from the Faculty of Mathematics and Natural Sciences at the State University of Malang. The study employed a quantitative descriptive. The method used was a survey. The instruments used were questionnaires for collaboration skills and tests for critical thinking and cognitive learning outcomes.  Data analysis was accomplished by computing the average value of the indicators. The computation results were then applied to the criterion table and categorized accordingly. The results showed that students' collaboration skills were characterized as very good, with more than 75% of students scoring excellent or good on each criteria. Students' critical thinking skills remained moderate, with more than 75% of students scoring moderately on application, analysis, and evaluation markers. Students' cognitive learning outcomes were still classed as moderate, with the majority of students scoring moderately on all indicators. İt can be concluded that student collaboration skills are categorized as excellent, students' critical thinking skills are categorized as intermediate, and students' cognitive learning outcomes remain moderate.